Pandangan Masyarakat Jepang terhadap Tokoh Transeksual dalam Film Karera ga Honki de Amu toki wa - Budi Mulyadi; Aida Kurniasih (Universitas Dian Nuswantoro, 2019)
This paper entitled the view of Japanese society towards transsexual character in the movie â€œKarera ga honki de amu toki waâ€. The main goal of this writing paper is to know about the view of Japanese society towards transsexual character which describedÂ in the movie Karera ga honki de amu toki wa. To analyze the description of heteronormativity in society that Naoko Ogigami wishes to convey in this film, we use the labeling theory in Narwoko and Suyanto and the literary sociology theory of Wellek and Warren by focusing on the second point, namely the sociology of literature. From the results of the analysis, it can be explained that the views of Japanese society on the transsexual figures portrayed in this film are not good. The act of labeling Rekso as a bad character in the film illustrates that there are still some Japanese people who have not accepted the existence of transsexuals. From the five aspects of sociology analyzed for this film, it can be concluded that although Japan is a country that is considered tolerant, they have not been able to fully accept transgender people in their social environment. Especially in aspects such as education, social and cultural aspects.Keywords: Film, Japanese Society, View, Transsexual, Character